Angiopoietin like protein 3 (Angptl3), fatty acid binding protein 4 (FABP4) and homeostasis model assessment of insulin resistance (HOMA-IR) among Indonesian obese non diabetic males (Medical Journal of Indonesia, 2010)
Aim To reveal the correlation between Angptl3, FABP4 and HOMA-IR among Indonesian obese non diabetic males. Methods This is a cross sectional study with 133 obese non diabetic males volunteers (characterized by waist circumference > 90 cm; fasting blood glucose < 126 mg/dL; and no diabetic specific symptoms) age between 30-60 years which was done in Jakarta, Indonesia. We measured biochemical markers such as Angptl3, FABP4, FFA, fasting insulin and fasting glucose. We also measured weight, height, waist circumference (WC), systolic blood pressure (SBP) and diastolic blood pressure (DBP). Correlation between each marker was measured using Pearson and Spearman's analysis. Results Pearson and Spearman's correlation analysis showed significant positive correlation between Angptl3 and FABP4 (r = 0.319; P = 0.000), Angptl3 and FFA (r = 0.171; r = 0.049), FABP4 and HOMA-IR (r = 0.202; P = 0.019), FFA and FABP4 (r = 0.506; P = 0.000), WC and HOMA-IR (r = 0.323; P = 0.000), WC and FABP4 (r = 0.387; P = 0.000), Body Mass Index (BMI) and HOMA-IR (r = 0.270; P = 0.002), BMI and FABP4 (r = 0.362; P = 0.000). Conclusion This study showed positive significant correlations between Angptl3-FABP4, Angptl3-FFA, FFA-FABP4 and FABP4-HOMA-IR. We suggest that Angptl3 can activate lipolysis in adipose tissue (through its correlation with FABP4), and Angptl3 concentration is related to insulin resistance risk among Indonesian obese non diabetic males. (Med J Indones 2010;19:185-90)